PENGEMBANGAN BAKAT SENI ANAK PADA TAMAN KANAK-KANAK - Putu Aditya Antara (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
This study aimed at finding out how learning develop the kindergarten children’s artistic talent and the factors related to the development of the artistic talents. This research was conducted in Ratna Kumara Kindergarten at the Medahan village, Blahbatuh, Gianyar, Bali involving 40 children. As a qualitative case study, this research collected data by observation, interviews, and document analysis. Data analysis used Spradley techniques. The results found out: (a) the artistic talent is developed through a child’s individual stimulation such as yoga, meditation, traditional games, singing, playing music and storytelling and in addition it can be done using social stimulation such as creative movement, role play, cooperative works; and (b) some factors supporting the success of children to develop their artistic talent that teachers should know such as the knowledge and understanding of children’s education, ability to create joyful learning, to show a close relationship and a good working team of fellow teachers, establish good communication and cooperation with parents, and the support of adequate learning facilities and comfortable healthy environment.